Astrocytes as critical players of the fine balance between inhibition and excitation in the brain: spreading depolarization as a mechanism to curb epileptic activity - Enger, Rune; Heuser, Kjell (Frontiers in Network Physiology, 2024)
Spreading depolarizations (SD) are slow waves of complete depolarization of brain tissue followed by neuronal silencing that may play a role in seizure termination. Even though SD was first discovered in the context of epilepsy research, the link between SD and epileptic activity remains understudied. Both seizures and SD share fundamental pathophysiological features, and recent evidence highlights the frequent occurrence of SD in experimental seizure models. Human data on co-occurring seizures and SD are limited but suggestive. This mini-review addresses possible roles of SD during epileptiform activity, shedding light on SD as a potential mechanism for terminating epileptiform activity. A common denominator for many forms of epilepsy is reactive astrogliosis, a process characterized by morphological and functional changes to astrocytes. Data suggest that SD mechanisms are potentially perturbed in reactive astrogliosis and we propose that this may affect seizure pathophysiology.